Mapping magnetospheric equatorial regions at Saturn from Cassini prime mission observations - Arridge,CS; André,N; McAndrews,HJ; Bunce,EJ; Burger,MH; Hansen,KC; Hsu,HW; Johnson,RE; Jones,GH; Kempf,S; Khurana,KK; Krupp,N; et al. (Space Science Reviews, 2011)
Saturn's rich magnetospheric environment is unique in the solar system, with a large number of active magnetospheric processes and phenomena. Observations of this environment from the Cassini spacecraft has enabled the study of a magnetospheric system which strongly interacts with other components of the saturnian system: the planet, its rings, numerous satellites (icy moons and Titan) and various dust, neutral and plasma populations. Understanding these regions, their dynamics and equilibria, and how they interact with the rest of the system via the exchange of mass, momentum and energy is important in understanding the system as a whole. Such an understanding represents a challenge to theorists, modellers and observers. Studies of Saturn's magnetosphere based on Cassini data have revealed a system which is highly variable which has made understanding the physics of Saturn's magnetosphere all the more difficult. Cassini's combination of a comprehensive suite of magnetospheric fields and particles instruments with excellent orbital coverage of the saturnian system offers a unique opportunity for an in-depth study of the saturnian plasma and fields environment. In this paper knowledge of Saturn's equatorial magnetosphere will be presented and synthesised into a global picture. Data from the Cassini magnetometer, low-energy plasma spectrometers, energetic particle detectors, radio and plasma wave instrumentation, cosmic dust detectors, and the results of theory and modelling are combined to provide a multi-instrumental identification and characterisation of equatorial magnetospheric regions at Saturn. This work emphasises the physical processes at work in each region and at their boundaries. The result of this study is a map of Saturn's near equatorial magnetosphere, which represents a synthesis of our current understanding at the end of the Cassini Prime Mission of the global configuration of the equatorial magnetosphere. © 2011 Springer Science+Business Media B